2017
DOI: 10.1177/1533034617708960
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cryosurgical Device Performance Using a 3D Tissue-Engineered Cancer Model

Abstract: As the clinical use of cryoablation for the treatment of cancer has increased, so too has the need for knowledge on the dynamic environment within the frozen mass created by a cryoprobe. While a number of factors exist, an understanding of the iceball size, critical isotherm distribution/penetration, and the resultant lethal zone created by a cryoprobe are critical for clinical application. To this end, cryoprobe performance is typically characterized based on the iceball size and temperature penetration in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 45 publications
(94 reference statements)
2
65
0
Order By: Relevance
“…Isothermal profiling of the frozen mass created by the epicardial cryoprobes revealed penetration of the -20°C, -30°C and -40°C isotherms to a diameter of 2.2 cm, 2.1 cm and 1.9 cm in a 2.3 cm iceball following a 3 minute freeze resulting in ~90% of the frozen volume below -20°C, 80% below -30°C and >65% below -40°C for the various SCN epicardial cryoprobe configurations (Table 4). This significantly outperformed previous reports on an argon cryodevice which was reported to yield ~35% and ~20% of the iceball being below -20°C and -40°C, respectively [53,61]. Other studies focusing on analysis of the -30°C isotherm have reported that an argon based cryoprobe produces ~25% of the frozen mass under -30°C under similar conditions [54,55].…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Isothermal profiling of the frozen mass created by the epicardial cryoprobes revealed penetration of the -20°C, -30°C and -40°C isotherms to a diameter of 2.2 cm, 2.1 cm and 1.9 cm in a 2.3 cm iceball following a 3 minute freeze resulting in ~90% of the frozen volume below -20°C, 80% below -30°C and >65% below -40°C for the various SCN epicardial cryoprobe configurations (Table 4). This significantly outperformed previous reports on an argon cryodevice which was reported to yield ~35% and ~20% of the iceball being below -20°C and -40°C, respectively [53,61]. Other studies focusing on analysis of the -30°C isotherm have reported that an argon based cryoprobe produces ~25% of the frozen mass under -30°C under similar conditions [54,55].…”
Section: Discussionmentioning
confidence: 54%
“…It is important to understand the model utilized and recognize the benefits and limitations in order to frame the results. Several studies have shown that the distribution of the -20°C and -40°C critical isotherms is often restricted to the center of the frozen mass (closest to the cryoprobe), thereby comprising less than 35% and 20% of the frozen mass, respectively (53)(54)(55)58,61,67) The typical freeze times reported in these and other studies range from 5 to 10 minutes which are applied in multiple (repeat) freeze/ thaw scenarios. While limited, these data provide a reference point for comparison of modern technologies.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations